The Curious Why - DiTerlizzi, Angela; Alvarez, Lorena (New York : Little, Brown and Company, 2024)
A magical friend called the Curious Why encourages children's imaginations to fly, as they consider "how, what, where and when?" in relation to the world around them.
new kids book 2024 spring.
Ages 4-8.
Keywords: Stories in rhyme; Imagination -- Fiction; Curiosity -- Fiction; Imagination & Play; Self-Esteem & Self-Reliance.; Self-esteem; Stories in rhyme; Picture books